2014
DOI: 10.1038/cdd.2014.117
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor β activation induces pyroptosis of human and murine colon cancer cells

Abstract: Liver X receptors (LXRs) have been proposed to have some anticancer properties, through molecular mechanisms that remain elusive. Here we report for the first time that LXR ligands induce caspase-1-dependent cell death of colon cancer cells. Caspase-1 activation requires Nod-like-receptor pyrin domain containing 3 (NLRP3) inflammasome and ATP-mediated P2 Â 7 receptor activation. Surprisingly, LXRb is mainly located in the cytoplasm and has a non-genomic role by interacting with pannexin 1 leading to ATP secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
139
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 30 publications
9
139
1
1
Order By: Relevance
“…However most of the experiments were performed on HCT116 infected with AdVP16LXRα [7] . We also noticed little effects of LXR agonists on apoptosis, but in our hands the majority of cell death induced by these ligands, involve a cell membrane permeabilization and caspase-1 activation [15] . Second, the cell type and the expression/localization of LXRα or LXRβ can dictate the incidence of LXR agonist treatment.…”
Section: Lxrα and βsupporting
confidence: 45%
See 3 more Smart Citations
“…However most of the experiments were performed on HCT116 infected with AdVP16LXRα [7] . We also noticed little effects of LXR agonists on apoptosis, but in our hands the majority of cell death induced by these ligands, involve a cell membrane permeabilization and caspase-1 activation [15] . Second, the cell type and the expression/localization of LXRα or LXRβ can dictate the incidence of LXR agonist treatment.…”
Section: Lxrα and βsupporting
confidence: 45%
“…ATP release, caspase-1 activation (and to a lesser extent late caspase-7 activation), chromatin fragmentation, cell swelling until becoming a balloon-shaped vesicle around the nucleus and membrane permeabilization. Moreover we did not observe any caspase-3, -8 or -9 activation in our settings [15] . Maybe the higher concentrations of LXR ligands used, can explain some of the differences observed with other studies.…”
Section: Lxrα and βcontrasting
confidence: 41%
See 2 more Smart Citations
“…More importantly, LXRs also serve non-genomic roles due to the differential cytoplasmic localization of LXRβ. LXRβ is predominantly located in the cytoplasm of colon cancer cells and induces pyroptosis when bound by ligand (26,27). Previously, a study revealed that LXR activation leads to cell cycle arrest in colon cancer cell lines.…”
Section: Effects Of Lxrs In Different Types Of Cancermentioning
confidence: 99%